The control and operation of the five level diode clamped inverter - Newton, Christopher (1999)
This thesis describes an investigation of three and five level diode clamped inverters for motor drive applications. The work was completed as a PhD project at the University of Nottingham with funding from EPSRC and Heenan Drives Ltd.